SURVEY OF PHARMACOLOGIC THROMBOPROPHYLAXIS IN CRITICALLY ILL CHILDREN - Faustino, Edward Vincent S. (2011)
OBJECTIVE: There is lack of evidence to guide thromboprophylaxis in the pediatric intensive care unit (PICU). We aimed to assess current prescribing practice for pharmacologic thromboprophylaxis in critically ill children. SETTING: PICUs in the United States and Canada with at least 10 beds. DESIGN: Cross-sectional self-administered survey of pediatric intensivists using adolescent, child and infant scenarios. PARTICIPANTS: PICU clinical directors or section heads. INTERVENTION: None. MEASUREMENTS AND MAIN RESULTS: Physician leaders from 97 of 151 (64.2%) PICUs or their designees responded to the survey. In mechanically ventilated children, 42.3% of the respondents would usually or always prescribe thromboprophylaxis for the adolescent but only 1.0% would prescribe it for the child and 1.1% for the infant. Considering all PICU patients, 3.1%, 32.0% and 44.2% of respondents would never prescribe thromboprophylaxis for the adolescent, child and infant scenarios, respectively. These findings were significant (P<.001 for the adolescent versus child and infant; P=.002 for child versus infant). Other patient factors that increased the likelihood of prescribing prophylaxis to a critically ill child for all 3 scenarios were the presence of hypercoagulability, prior deep venous thrombosis or a cavopulmonary anastomosis. Prophylaxis was less likely to be prescribed to patients with major bleeding or an anticipated invasive intervention. Low molecular weight heparin was the most commonly prescribed drug. CONCLUSIONS: In these scenarios, physician leaders in PICUs were more likely to prescribe thromboprophylaxis to adolescents compared to children or infants, but they prescribed it less often in adolescents than is recommended by evidence-based guidelines for adults. The heterogeneity in practice we documented underscores the need for rigorous randomized trials to determine the need for thromboprophylaxis in critically ill adolescents and children.